PENGEMBANGAN SISTEM PEMANTAUAN CERDAS KINERJA PENGAWAS SEKOLAH - FAUZAN AKHMAD MAHANANI (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2022)
The performance of school supervisors in carrying out academic and managerial supervisory duties in education units which includes the preparation of supervision programs, implementation of guidance, monitoring of the implementation of National Education Standards, assessment, mentoring is very important in maintaining and improving the quality of education. The purpose of this study was to determine the stages of developing an information system for monitoring the performance of school supervisors based on information technology at the Department of Youth and Sports Education, Banjarnegara Regency. The information system developed was named “Sipedas” which is an acronym for sistem Informasi pemantauan cerdas. The research method used in this research is the Research and Development (R&D) method. In the analysis combines qualitative and quantitative data to find out how much the utilization of the Sipedas information system is used. The average usability test results of Sipedas show more than 72% of user respondents' answers stating that Sipedas is "Good". Based on the development, testing and analysis, it can be concluded that Sipedas is feasible and effective to be used in the process of monitoring the performance of school supervisors in terms of usability. ABSTRAKKinerja pengawas sekolah dalam melaksanakan tugas pengawasan akademik dan manajerial pada satuan pendidikan yang meliputi penyusunan program pengawasan, pelaksanaan pembinaan, pemantauan pelaksanaan Standar Nasional Pendidikan, penilaian, pembimbingan sangat penting dalam menjaga dan meningkatkan mutu pendidikan. Tujuan penelitian ini adalah untuk mengetahui proses pengembangan sistem informasi pemantauan kinerja pengawas sekolah berbasis teknologi informasi di Dinas Pendidikan Kepemudaan dan Olahraga Kabupaten Banjarnegara. Sistem informasi yang dikembangkan ini diberinama “Sipedas” yang merupakan akronim dari sistem Informasi pemantauan cerdas. Metode penelitian yang digunakan dalam penelitian ini adalah metode Research and Development (R&D). Dalam analisis menggabungkan data kualitatif dan kuantitatif untuk mengetahui seberapa besar pemanfaatan sistem informasi Sipedas digunakan. Rata-rata hasil uji ketergunaan (usability) Sipedas menunjukan 72% lebih jawaban responden pengguna menyatakan bahwa sipedas “Baik”. Berdasarkan pengembangan, pengujian dan analisis dapat disimpulkan bahwa Sipedas layak dan efektif digunakan pada proses monitoring kinerja pengawas sekolah ditinjau dari uji ketergunaan (usability).